2011
DOI: 10.1016/j.healun.2011.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Troponin I levels from donors accepted for pediatric heart transplantation do not predict recipient graft survival

Abstract: Background Troponin I (TnI) is often obtained during evaluation of a potential transplant donor heart. It is unclear whether elevations in donor TnI levels predict adverse outcomes and should thus preclude acceptance of a donor heart. The aim of this study was to examine whether TnI levels from donors accepted for pediatric heart transplantation predict graft failure. Design/Methods De-identified data on heart transplants performed in recipients ≤ 21 years old between 4/07-4/09 was provided by the Organ Proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Another recent report mentions that the number of transplant centers requesting donor troponin levels before accepting a donor heart for transplant has increased by a large extent over the past several years without any particular strategy in place to understand the implications, if any, of the donor troponin levels given. The analysis shows that elevated troponin levels in donors prior to procurement are not associated with increased incidence of graft failure (10). Regarding travel distance leading to increased graft ischemic times, there are contradictory reports for adult transplants; however, several pediatric reports have shown no association between graft ischemic time and recipient post-transplant survival (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Another recent report mentions that the number of transplant centers requesting donor troponin levels before accepting a donor heart for transplant has increased by a large extent over the past several years without any particular strategy in place to understand the implications, if any, of the donor troponin levels given. The analysis shows that elevated troponin levels in donors prior to procurement are not associated with increased incidence of graft failure (10). Regarding travel distance leading to increased graft ischemic times, there are contradictory reports for adult transplants; however, several pediatric reports have shown no association between graft ischemic time and recipient post-transplant survival (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac troponin levels (troponin T or I) have greater sensitivity and specificity for myocardial injury (248). One study suggested that the assessment of isoform might be useful in the evaluation of a marginal (i.e., extended criteria) heart donor and might serve as a prognostic indicator of posttransplant myocardial outcome (249), but other studies have demonstrated conflicting data, finding no clear relationship (250,251). Furthermore, there appears to be no threshold value above which a heart with normal echocardiographic parameters could not be utilized nor does serial evaluation of troponin I levels appear to hold any value (252,253).…”
Section: Is There Any Value To Monitoring Cardiac Enzymes?mentioning
confidence: 99%
“…23 More recently, a study demonstrated that troponin I levels in a potential transplant donor heart were not correlated with post-transplant hospital length of stay and graft status. 24 High-sensitivity troponin assays are defined differently by different groups, although some in the biomarker community advocate a definition of these assays as assays that detect troponin in the blood of 50% or more of apparently healthy adults. 25 Potter et al 26 also found that transient elevations of high-sensitivity troponin T did not correlate with any cardiac disease in healthy young children.…”
Section: Troponinsmentioning
confidence: 99%